Sexual polyploidization in plants – cytological mechanisms and molecular regulation - De Storme, Nico (Blackwell Publishing Ltd, 2013)
In the plant kingdom, events of whole genome duplication or polyploidization are generally believed to occur via alterations of the sexual reproduction process. Thereby, diploid pollen and eggs are formed that contain the somatic number of chromosomes rather than the gametophytic number. By participating in fertilization, these so-called 2n gametes generate polyploid offspring and therefore constitute the basis for the establishment of polyploidy in plants. In addition, diplogamete formation, through meiotic restitution, is an essential component of apomixis and also serves as an important mechanism for the restoration of F1 hybrid fertility. Characterization of the cytological mechanisms and molecular factors underlying 2n gamete formation is therefore not only relevant for basic plant biology and evolution, but may also provide valuable cues for agricultural and biotechnological applications (e.g. reverse breeding, clonal seeds). Recent data have provided novel insights into the process of 2n pollen and egg formation and have revealed multiple means to the same end. Here, we summarize the cytological mechanisms and molecular regulatory networks underlying 2n gamete formation, and outline important mitotic and meiotic processes involved in the ectopic induction of sexual polyploidization.